2016
DOI: 10.1590/1678-4162-8327
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surface temperatures of buffalo bulls (Bubalus bubalis) raised under tropical conditions using infrared thermography

Abstract: Assessment of surface temperatures of buffalo bulls (Bubalus bubalis) raised under tropical conditions using infrared thermography ABSTRACTThis paper aimed to evaluate the surface temperatures of buffalo bulls using infrared thermography, considering four distinct anatomical parts over time, and to correlate surface temperatures and thermal comfort indexes. The humid tropical climate (Köppen's Afi) was predominant in the research station where the experiment was performed and the trial lasted from April to Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 19 publications
3
50
1
2
Order By: Relevance
“…The vulva, muffle and orbital area surface temperatures (measured by IDT) and the rectal temperatures obtained in the present study are similar to previous studies in dairy cows (Talukder et al, 2014;Chacur et al, 2016b) and dairy buffalo (Barros et al, 2016;Sevegnani et al, 2016). Thus, the IDT technique is of potential applicability in the study of the physiological modifications of body temperature in buffalo.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The vulva, muffle and orbital area surface temperatures (measured by IDT) and the rectal temperatures obtained in the present study are similar to previous studies in dairy cows (Talukder et al, 2014;Chacur et al, 2016b) and dairy buffalo (Barros et al, 2016;Sevegnani et al, 2016). Thus, the IDT technique is of potential applicability in the study of the physiological modifications of body temperature in buffalo.…”
Section: Discussionsupporting
confidence: 90%
“…The applicability of IDT in buffalo has recently been demonstrated. It was verified that the skin temperatures of the orbital area, flank and ears are subject to weather variations and correlated with rectal temperature and can be used in studies of thermal comfort in these animals (Barros et al, 2016;Sevegnani et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…Several authors reported that insulation and the appearance of sperm pathologies after insult depend on the duration of tissue damage that will contribute to the great diversity of results displayed when testis are subjected to heat stress (Brito, Silva, Barbosa, & Kastelic, ; Kastelic et al., 1996b). Indeed, the use of IRT is an important noninvasive technique to evaluate thermoregulation in many species and has been previously described using this methodological approach in bulls (Barros et al., ; Neto et al., ; Rodrigues‐Alves et al., ; Ruediger et al., ; Vencato et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…IRT is widely used to identify localized areas of inflammation, such as mastitis in lactating cows [17-19], foot and mouth disease [20], assessment of tissue damage and healing due to hot versus cold branding in cattle [21], Laminitis [7,8], detection of bovine viral diarrhea in calves [22], monitoring respiratory disorders [23], Actinobacillus pleuropneumoniae infection in pigs [24], detection of estrus and prediction of ovulation in cattle and gilts [5,6,25,26], to assess the effect of scrotal temperature on sperm production in bulls [27-29], assessing meat quality in pigs [30], for identification of stress [31], measurement of feather cover [32], effects of machine milking on teat and udder [33], surface temperature, estimation of heat and methane production in dairy cattle [34], screening of cattle for feed utilization efficiency [9,35], pregnancy diagnosis in mare and wild animals [36,37], evaluation of thermal status of neonatal pigs [38], monitoring stress during animal transit and welfare in wild animals [39], assessment of surface temperature of buffaloe bulls and its correlation with rectal temperature [40] and for the evaluation of thermoregulatory capacity of dairy buffaloes [41]. …”
Section: Application Of Irt In Veterinary Medicinementioning
confidence: 99%